Comparison of conventional and transgenic soybean production costs in different regions in Brazil (Research, Society and Development, 2020)
The soybean crop is one of the most economically important crops in Brazilian agribusiness and in the world, with the expansion of the crop always linked to scientific advances and new production technologies. In view of the above, the objective of this study was to evaluate the production costs of twenty-one producing regions to determine the highest and lowest production costs in the first harvest in three agricultural years and in the summer harvest in two agricultural years, with the conventional and transgenic soybeans, in addition to comparing the cost of production of the cultivation systems. As for technical procedures, a descriptive research was carried out with statistical data provided by the National Supply Company. The agricultural years of 2018, 2019 and 2020 of soybean culture were analyzed in twenty-one Brazilian municipalities, located in the Brazilian states: Bahia, Distrito Federal, Goiás, Maranhão, Mato Grosso, Mato Grosso do Sul, Minas Gerais, Paraná, Piauí , Rio Grande do Sul, Roraima and Tocantins. The region of Primavera do Leste - MT demonstrated a region with a high cost of production in comparison with other producing regions. The lowest costs varied between several regions, depending on the cultivation system employed. The production of transgenic soybeans proved to be the most profitable and promising option due to the lower production cost in relation to the cultivation of conventional soybeans.